Strategi Pengelolaan Aset Desa Berbasis Aplikasi Sistem Pengelolaan Aset Desa (Sipades) Di Desa Kekeri Kecamatan Gunungsari Kabupaten Lombok Barat - Adheitya Widaniyansyah, Adheitya; Martiningsih, Rr Sri Pancawati; Suryantara, Adhitya Bayu (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research is based on the results of observations which found several problems in the Village Asset Management Strategy Based on the "SIPADES" Village Asset Management System Application in Kekeri Village, Gunungsari District, West Lombok Regency, namely: Lack of direction from the Social, Community and Village Empowerment Service regarding guidelines for using the System application Village Asset Management, there is no special emphasis on the use of the Village Asset Management System application, there is no updating of the Village Asset Management System application every year. The aim of this research is to determine the Village Asset Management Strategy Based on the "SIPADES" Village Asset Management System Application in Kekeri Village, Gunungsari District, West Lombok Regency. This research is a descriptive study with a qualitative approach. To obtain information and data, researchers used semistructured interviews and documentation methods. The inhibiting factors were lack of budget due to not having original village income and funds not being received on time, lack of guidance and competency improvement from related agencies, the Sipades application had not been running optimally and was still not can access. Efforts made to overcome obstacles include budgeting a larger budget, seeking budget from other income by increasing the PADes or from third party donations and further efforts by exchanging budget functions first, holding training related to village asset management and bringing in parties related to village asset management to provide guidance to village officials, BPD, LPM budgeted from the APBDes.